If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 6c = 52 Solving 10 + 6c = 52 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 6c = 52 + -10 Combine like terms: 10 + -10 = 0 0 + 6c = 52 + -10 6c = 52 + -10 Combine like terms: 52 + -10 = 42 6c = 42 Divide each side by '6'. c = 7 Simplifying c = 7
| 2x+25=3x-13-x | | 7x-6+8x=19 | | 9w-4=77 | | -6x^2+11x+10=0 | | -8p+3=29 | | 3x+5x-5+9-2x= | | 2ax+3y=13 | | 3m^2+12m+7=0 | | 2x-8=6x+12 | | X^2+2x-600=0 | | 2x-8=6x+13 | | 3a^2+11ab-4b^2= | | -2x+3+3x-9= | | v+27.4=194.9 | | 7-(3x+2)=2x-11+3x | | -2+3+3x-9= | | v-30.1+v+27.4=194.9 | | v+v-30.1+v+27.4=194.9 | | 3y-12=21 | | 4x-7=8x+21 | | 7m-2n=2 | | 1x+3x-(7x+10)= | | (x-4)-(4x+4)= | | 32x+16=-43 | | (x-4)+(4x+4)= | | -3(2s-4)-12=-3(8s+6)-4 | | y+y*0.1+y*0.07=117 | | 3(-1)+2(3)=6 | | 2x+36=9x+153 | | -2x+8y=-20 | | v+v-31.8+v+26.4=198.0 | | 2a^2+9a+4=0 |